A new marine woodground ichnotaxon from the Lower Cretaceous Mannville Group, Saskatchewan, Canada. (January 2021) - Melnyk, Scott; Packer, Stephen; Zonneveld, John-Paul; Gingras, Murray K.
Abstract: A new wood-boring ichnospecies is described from transgressive (lagoonal) deposits of the Lower Cretaceous Sparky Formation (Mannville Group) in west-central Saskatchewan, Canada. Apectoichnus lignummasticans new ichnospecies is a trace fossil that occurs in a thin coal bed and that was emplaced in an in situ xylic substratum (woodground). The ichnofossil is thin, elongate, unbranched, and straight to gently curved with a circular cross section and uniform diameter. Apectoichnus lignummasticans n. isp. is similar in many respects to modern borings in wood that are produced by marine isopods, e.g., Limnoria lignorum Rathke, 1799, for feeding and refugia. The recognition of Apectoichnus lignummasticans n. isp. in the rock record aligns with the modern observation that fossilized wood-boring assemblages should display higher ichnofossil diversities than commonly reported. Additionally, the stratigraphic occurrence of Apectoichnus lignummasticans n. isp. in association with other evidence of marine deposition reaffirms that certain wood boring morphologies (i.e., ichnotaxa) are useful as indicators of marine transgressions. UUID: http://zoobank.org/880e722f-8944-42d7-bc38-423cc5a46413